INNOVATION AND DEVELOPMENT OF MULTIMODAL LEARNING MEDIA: A LITERATURE STUDY ON THE INTEGRATION OF PRINT, AUDIOVISUAL, AND COMPUTER TECHNOLOGY TO IMPROVE THE QUALITY OF 21ST CENTURY LEARNING PROCESSES - Zulvia Trinova; Mowafg Masuwd; Aslan Aslan (Review of International Journal Education and School Leadership, 2025)
This study aims to systematically examine the concepts, theories, and practices of multimodal learning media innovation as a strategy for improving the quality of 21st-century learning. This study uses a library research method by examining various scientific sources such as journals, proceedings, and textbooks that discuss the integration of print, audiovisual, and computer technology media. The results of the study show that multimodal learning is based on the Cognitive Theory of Multimedia Learning and the social semiotics approach, which emphasises the importance of combining various modes of communication in constructing meaningful understanding. The integration of print, audiovisual, and computer technology media produces pedagogical synergy that can strengthen motivation, improve cognitive effectiveness, and support collaborative and independent learning. The application of multimodality in learning media design has been proven to support the development of 21st-century competencies such as critical thinking, creativity, communication, and digital literacy. Thus, multimodal learning media can become a strategic foundation for the renewal of a modern education system that is adaptive to technological developments and the learning needs of students.